9.2k views
4 votes
I have a problem. I have a picture of it because I can't type it

I have a problem. I have a picture of it because I can't type it-example-1
User Caldazar
by
5.6k points

1 Answer

3 votes

we have the next equation


5x^2-36x+36=0

we will use the formula to find the values of x of a second-grade equation


x_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

where

a=5

b=-36

c=36

we substitute the values in the formula


x_(1,2)=\frac{36\pm\sqrt[]{36^2-4(5)(36)}}{2(5)}=\frac{36\pm\sqrt[]{576}}{10}=(36\pm24)/(10)
x_1=(36+24)/(10)=(60)/(10)=6
x_2=(36-24)/(10)=(6)/(5)

the values of x are

x=6 and x=6/5

User Kiran Modini
by
5.7k points